MAQASHID AL-QUR’AN DAN INTERPRETASI WAṢFĪ ‘ĀSYŪR ABŪ ZAYD - Muchammad Harun Arrosyid (PT. Hasba Edukasi Mandiri, 2025)
Maqashid al-Qur'an is a new discourse in the study of the Qur'an. Scholars are still debating his position in the study of the science of Ulum al-Qur'ān. Is it a separate discipline or is it part of another science. Many interpretation products are not oriented to Maqashid and are only a repetition of the products of previous interpretations or contestation of interpretations of thought. Therefore, the main object of this study is to provide a deeper understanding of the study of Maqashid al-Qur'an and how to apply the Maqashidi interpretation of Waṣfī, an Egyptian cleric. This research is a qualitative research and library research with a sociology of knowledge approach. The primary data of this research are the works of Waṣfī and the results of interviews. According to Waṣfi, the purpose of the Qur'an is the realization of the purpose of the surah, verse, and theme in the Qur'an. He asserted that the Maqashid al-Qur'an consists of five parts: general and specific objectives (Maqashid 'Āmmah and Maqashid Khāṣṣah), the purpose of surahs, verses, words, and letters in the Qur'an and according to him Maqashidi interpretation apart from being one of the various interpretations independently, it also penetrates and integrates into all the various interpretations that exist. Maqashidi interpretation is a style, perspective, as well as a variety of interpretations. The idea is unique because of the exclusivity in the variety of Maqashid and the method in finding the Maqashsid of the Qur'an.